PENGARUH ETHICAL COMPETENCY DAN STRATEGIC COMPETENCY TERHADAP PERTUMBUHAN BISNIS MAHASISWA - Utomo, Budi; Trisnawati, Desi (Gapenas Publisher, 2025)
This study examines the influence of ethical competency and strategic competency on student business growth. Ethical competency refers to the ability of students to apply ethical values in business decision-making, while strategic competency involves the capacity to plan and execute effective business strategies. Using a quantitative approach, the study surveyed 101 student entrepreneurs from the Faculty of Islamic Economics and Business, UIN Salatiga. Data were collected through questionnaires and analyzed using SPSS. The results reveal that both ethical and strategic competencies significantly contribute to business growth. Students with strong ethical competency tend to make responsible and transparent decisions that enhance long-term performance, while those with strong strategic competency demonstrate greater adaptability and sustainability. These findings emphasize the importance of integrating ethical and strategic competency development into entrepreneurship education programs. It is hoped, the study recommends that entrepreneurship education should strengthen students’ ethical and strategic skills through practical learning, mentoring, and business incubation programs. Universities should provide continuous support, monitoring, and training to help students make responsible decisions and develop effective strategies. Additionally, opportunities for networking, collaboration, and hands-on business experience should be expanded to enhance students’ readiness and long-term business growth